A moving scene on the Road to Slane. - Heath, William, 1795-1840 - also known as Paul Pry (McLean, Thomas, 1830)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Henry Conyngham, 1st Marquess Conyngham ?; Slane Castle; Ireland -- Politics and government -- 1800-1837; Conyngham, Elizabeth Conyngham, Marchioness, d. 1861